Perlindungan Hukum terhadap Korban Pelecehan Seksual di Indonesia: Analisis Efektivitas dan Hambatan Penegakan Hukum - Daniel Hagana Bangun; Gunawan Widjaja (International Forum of Researchers and Lecturers, 2026)
Sexual violence represents a fundamental infraction of human rights, generating profound physiological, psychological, and social ramifications for the victims. This study aims to critically evaluate the efficacy of current legal protections designated for victims of sexual harassment in Indonesia, while simultaneously mapping the institutional impediments within the prosecution of perpetrators. Employing a doctrinal legal methodology (normative juridical), this research relies exclusively on secondary legal sources, specifically conducting a comparative analysis between the legacy Penal Code (KUHP Lama) and the newly enacted National Penal Code (KUHP Nasional). The analytical framework is constructed through a statutory and conceptual approach. The empirical findings elucidate that despite substantial legislative updates, the practical adjudication of sexual offenses consistently encounters multi-dimensional bottlenecks spanning substantive law limitations, deep-rooted cultural biases, and lack of gender-sensitive law enforcement. Although the newly codified Penal Code introduces expanded definitions and enhanced victim safeguards, its ultimate success remains heavily contingent upon systemic implementation at the operational level.